2010
DOI: 10.1021/pr900863u
|View full text |Cite
|
Sign up to set email alerts
|

Value of Using Multiple Proteases for Large-Scale Mass Spectrometry-Based Proteomics

Abstract: Large-scale protein sequencing methods rely on enzymatic digestion of complex protein mixtures to generate a collection of peptides for mass spectrometric analysis. Here we examine the use of multiple proteases (trypsin, LysC, ArgC, AspN, and GluC) to improve both protein identification and characterization in the model organism Saccharomyces cerevisiae. Using a data-dependent, decision tree-based algorithm to tailor MS2 fragmentation method to peptide precursor, we identified 92,095 unique peptides (609,665 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
462
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 422 publications
(492 citation statements)
references
References 32 publications
22
462
0
8
Order By: Relevance
“…For Drosophila melanogaster, adding a fractionated adult sample to the spectral library increased the number of proteins in the library from 5,335 to 6,040 showing that adding specific tissue/developmental stage is useful to increase the size of spectral libraries for SWATH-MS. The peptide size distributions are very similar for both spectral libraries with a high proportion of peptides around 10 amino acids long ( Figure S2) which is in agreement with previous study using trypsin in yeast [23]. Our spectral libraries cover around 34% and 15% of the expected proteomes of Drosophila melanogaster and Solanum lycopersicum which, to our knowledge, constitute the most complete spectral libraries acquired on TripleTOF instruments for either species.…”
supporting
confidence: 89%
“…For Drosophila melanogaster, adding a fractionated adult sample to the spectral library increased the number of proteins in the library from 5,335 to 6,040 showing that adding specific tissue/developmental stage is useful to increase the size of spectral libraries for SWATH-MS. The peptide size distributions are very similar for both spectral libraries with a high proportion of peptides around 10 amino acids long ( Figure S2) which is in agreement with previous study using trypsin in yeast [23]. Our spectral libraries cover around 34% and 15% of the expected proteomes of Drosophila melanogaster and Solanum lycopersicum which, to our knowledge, constitute the most complete spectral libraries acquired on TripleTOF instruments for either species.…”
supporting
confidence: 89%
“…Alkylation was quenched by a 15-min incubation in 5 mM dithiothreitol at room temperature. This was followed by a multiple protease approach, utilized to maximize protein sequence coverage (45), and involved addition of five different proteases (individually or sequentially) (see the details in the supplemental Experimental Procedures).…”
Section: Digestion Of Pro-␣1(v) and ␣1(v) Samples For Mass Spectrometmentioning
confidence: 99%
“…The enabling technology was an ETD-enabled LTQ Orbitrap Velos hybrid mass spectrometer exhibiting low ppm mass accuracy, high resolution MS, and MS n capabilities combined with multiple options for performing peptide dissociation (47). We began by using multiple proteases to generate a diverse pool of peptides amenable to MS n (45). The combination of mass accuracy and a capability to perform multistage activation using three different dissociation techniques often allowed us to pinpoint the exact residue(s) carrying individual PTMs.…”
Section: A High Mass Accuracy High Resolution Tandem Mass Spectrometmentioning
confidence: 99%
“…It had been shown that the use of multiple proteases could remarkly increase the sequence coverage of identified proteins for large-scale proteomics analysis. 15 The lowspecificity proteases such as elastase, proteinase K, and thermolysin had been used for in-depth mapping of phosphorylation sites of murine circadian protein period 2; a total of 21 phosphorylation sites were identified from this protein, whereas only 6 sites were identified by trypsin. 16 The low-specificity protease elastase had been used together with trypsin for phosphoproteome analysis of mitotic spindle proteins; 17 the overlap of phosphorylation sites identified by the two proteases was less than 10%.…”
Section: ■ Introductionmentioning
confidence: 99%